Smart leadership and its relationship to decision-making for some handball coaches fromthe players' point of view - ريم عباس كريم أ.د انتصار عويد (physical education and sport sciences college for women/ Baghdad University, 2021)
Search to identify the following: Learn about the relationship between learning to read some part-time football Premier League shots. The researcher used the descriptive approach using a survey study method and correlational relations, and the research community identified the players of some of the Iraqi Premier League. Their number is (154). - Al-Khaleej - Al-Raid - Sulaymaniyah - Al-Musayyib), then a sample of (56) aircraft was randomly selected from them, and they are club players (Army - Police - Karbala - Fatwa). I examined them with a smart leadership decision and after the results showed that: - Some coaches of the Iraqi Premier Handball League clubs enjoy a high level of intelligent leadership and decision-making. There is a direct correlation between smart leadership and decision-making. Therefore, the researcher recommends: - Developing the skills of coaches of the Iraqi Premier Handball League clubs and enhancing their skills and abilities by improving their abilities and skills in the field of emotional, rational and spiritual intelligence by involving them in training courses in which intelligence and its types represented by emotional, rational and spiritual intelligence are the main topic. • Adopting the IQ standard in selecting the trainer, and that coaches are changed according to specific time periods in order to inject new ideas and intelligences that work to develop and improve the team's results